Sustainable Development of Society and Russian Philosophy: Educational Aspect - Gerasimova, Evgenia N.; Usachev, Aleksandr V.; Usacheva, Irina N.; Shcherbatykh, Sergey V. (International Journal of Criminology and Sociology, 2021)
The purpose of the article is to project the general statements of the philosophical tradition and domestic psychological schools of thought on the specific situation of teaching and education, as well as to compare the historically emerging ideas of upbringing and education with modern approaches, and to trace the genetic connection and the continuity of ideas. In this context, it is possible to draw conclusions and learn lessons for the development of the modern pedagogical situation. The research results are novel and practically significant, since the main conclusion is the choice of a methodological basis for teaching natural sciences with a view to the sustainable development of society as a whole and within the framework of subject-subject relationship in particular. According to the chosen methodology, teaching information about sustainable development involves a set of interconnected methods for the purpose of their application in the educational process so to access each student individually. A special contribution of the authors is a comparative analysis of approaches to training and education, which result in the sustainable development of society.